The influence of job stress, job demands, and motivation on job satisfaction of Bantul Community Health Center Employees II - Dewi, Yunita; Armono, R. Drajat; Fatimah, Fatia (Nur Science Institute, 2024)
This study aims to determine how Bantul II Community Health Center employees' motivation, job demands, and work stress affect their job satisfaction. This study is conducted using a quantitative method. The study involves verification research, which tests current hypotheses to support or contradict earlier findings. This research was attended by 45 respondents from the Bantul II Community Health Center, which used a total sample method. A Likert scale questionnaire served as the study instrument, and multiple linear regression analysis was employed to analyze the data. The impact of work-related stress on Bantul II Community Health Center employees' job satisfaction is unfavorable and substantial. The work obligations placed on Bantul II Community Health Center personnel favorably and considerably impact their job happiness. Bantul II Community Health Center employees report higher levels of work satisfaction when they are motivated. The factors that concurrently impact the job happiness of Bantul II Community Health Center personnel are work stress, job demands, and motivation.